2021
DOI: 10.1111/hel.12807
|View full text |Cite
|
Sign up to set email alerts
|

Oral multivalent epitope vaccine, based on UreB, HpaA, CAT, and LTB, for prevention and treatment of Helicobacter pylori infection in C57BL / 6 mice

Abstract: Background As the resistance of Helicobacter pylori to traditional triple therapy is gradually revealed, an increasing number of people are focusing on vaccine treatments for H. pylori infection. Epitope vaccines are a promising strategy for the treatment of H. pylori infection, and multivalent vaccines will be more effective than monovalent vaccines. Materials and methods In this study, we designed a multivalent vaccine named LHUC, which consists of the adjuvant LTB as well as three Th cell epitopes (HpaA154‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Studies have demonstrated that the naturally occurring antibodies, particularly IgA, could prevent infection of H. pylori. (11) The sIgA improves bacterial opsonization and inhibits bacterial adherence and colonisation. (12) In order to fight off the pathogenic bacteria, the host's adaptive oral immune mechanisms are likely involved in HP infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that the naturally occurring antibodies, particularly IgA, could prevent infection of H. pylori. (11) The sIgA improves bacterial opsonization and inhibits bacterial adherence and colonisation. (12) In order to fight off the pathogenic bacteria, the host's adaptive oral immune mechanisms are likely involved in HP infection.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have reported that saliva is a noninvasive sample for detection and attractive option for epidemiologic studies because it has been analyzed and obtained easily, collection and testing salivary specimens is fast, painless, convenient, and carries no risk of needle stick injury (10) . The salivary PH and flow rate in study were higher in study group than normal values in healthy control group, the pH value of unstimulated saliva is acidic which ranges between (5.75 -7.05), it becomes more when the flow rate was increased and may reach a PH at high flow rate, in addition to the flow rate, the pH also depends on the salivary proteins concentration, phosphate (PO43−) ions and bicarbonate (HCO3−) that have considerable buffering capacity for maintaining the PH level in saliva (11). The esophago-salivary reflex may be affected by the acidic gastric content that refluxing into esophageal lumen which causes damage to esophageal mucosa, all these changes lead to stimulates salivary secretion and changes the concentration of some of saliva constituents.…”
Section: Discussionmentioning
confidence: 99%
“…A prophylactic or therapeutic vaccine needs the selection and combination of immunogenic bacterial antigens with effective adjuvants and its administration via an available route [ 109 ]. The main antigens related to vaccines are CagA, VacA, BabA, HpaA, NapA, OipA, GGT, HspA, Omp, and FliD [ 110 ], and their combinations of multivalent epitopes with adjuvants, usually composed of CD4 + and CD8 + epitopes [ 111 ] (e.g., CTB-UE, CWAE vaccine [ 112 ], CFdAE vaccine [ 113 ], FVPE vaccine [ 114 ], HUepi-LTB vaccine [ 115 ], LHUC-LTB [ 116 ], and CTB-HUUC vaccine [ 117 ]). Some vaccines have been developed, such as oral delivery of either whole cell or subunit vaccines in combination with cholera toxin and Escherichia coli enterotoxin as mucosal adjuvant to increase the immunogenicity, oral delivery of live vector vaccines expressing H. pylori antigens to stimulate durable immunity (e.g., avirulent strains of Salmonella and attenuated Listeria monocytogenes ), and intramuscular delivery of H. pylori subunits vaccines with aluminum hydroxide adjuvant [ 118 120 ].…”
Section: Potential Alternative Treatment Strategiesmentioning
confidence: 99%
“…Urease is also a main antigen in vaccines, and UreB is considered as the most suitable for urease‐recombinant vaccines 23 . Oral multivalent epitope vaccine combining UreB and Th/B cell epitopes with novel adjuvants was found safe and effective in the mice model 24–26 …”
Section: Introductionmentioning
confidence: 99%
“…23 Oral multivalent epitope vaccine combining UreB and Th/B cell epitopes with novel adjuvants was found safe and effective in the mice model. [24][25][26] When encountering the suitable niche, H. pylori will establish the persistent colonization, and subsequently cause gastric or extra-gastric diseases. 1%-3% H. pylori infected patients may develop gastric cancer (GC) accounting for 90% of non-cardia GC (NCGC) and 20% of cardia GC (CGC) with adjusted hazard ratios of 5.94 for NCGC and 3.06 for CGC, which accounts for 15% of the total cancer burden globally.…”
mentioning
confidence: 99%